Investigating the impact of a genome-wide supported bipolar risk variant of MAD1L1 on the human reward system - Trost, Sarah; Krämer, Bernd; Gruber, Oliver (Neuropsychopharmacology, 2016)
Investigating the Impact of a Genome-Wide Supported Bipolar Risk Variant of MAD1L1 on the Human Reward System